Hubungan Karakteristik Ibu Dengan Kejadian BBLR Di RSUD Kota Yogyakarta - Fatimah Izhara; Prasetya Lestari; Lia Dian Ayuningrum; Fatimah (LPPM - STIKES Pemkab Jombang, 2025)
According to the Ministry of Health of the Republic of Indonesia, the prevalence of low brith weight in Indonesia in 2023 is 3.9%. The causes of preterm birth and LBW are caused by maternal factors such as maternal age, gestational age, parity, education level, and medical history. The purpose of this study was to determine the relationship between maternal characteristics and the incidence of LBW in Yogyakarta City Hospital. This type of research analytic observational with a cross sectional approach. The study population was mothers giving birth at Yogyakarta City Hospital in the period January-November 2024 using total sampling technique obtained a sample of 146 respondents. Instruments in the form of medical records. Data analysis used univariate and bivariate analysis (chi square test and fisher exact test). Univariate analysis showed the majority of maternal characteristics were 20-35 years old (78.8%), high school / vocational school education (54.1%), respondents did not have a history of disease (62.3%), gestational age 37-42 weeks (77.4%), grandemultiparous parity (59.6%) and the majority were first-time mothers (no pregnancy gap) (39.7%), Meanwhile, bivariate analysis showed that there was a relationship between gestational age (p=0.000) and the incidence of LBW in Yogyakarta City Hospital and there was no relationship between maternal age (p=0.608), education (p=0.476), disease history (p=0.449), parity (p=0.139) and gestational distance (p=0.173) with the incidence of LBW. The conculation there is a relationship between maternal characteristics in gestational age and the incidence of LBW, and there is no relationship between maternal age, education, history of disease, parity, pregnancy distance with the incidence of LBW at Yogyakarta City Hospital.